Characteristics of Selected Network Attacks on a University Unit in Poland - Grzegorz PODGORSKI (Communications of International Proceedings, 2021)
The aim of the article will be to present the results of research related to network attacks on a university unit in the period from April 2020 to April 2021 during the pandemic in Poland. The types of attacks and their nature will be analyzed. The change in the attack vector in the context of the duration of the pandemic will also be analyzed. The article consists of two parts. The first one is theoretical. The second is a case study of an educational organization along with an analysis of selected networks attacks. Universities as public research and education centers are particularly vulnerable to all kinds of network attacks. The analysis of network attacks on a university unit in the context of information security allows for tangible benefits, especially in increasing the level of information security. It also allows to define the types of threats such units have to face. It also gives the possibility to fine-tune and better adapt existing security solutions or implement new ones. The article contains a case study of a university unit in Poland in terms of threats related to network attacks. The article presents the actual data collected over a period of one year on network threats that have been registered in the organization. Conclusions were also drawn related to the relationship of network attacks in the context of the coronavirus pandemic and the transition to the remote working model.
Keywords: Case Study; Network Attacks; Information Security